The Effect of Exposure to Gamma Radiation And Giving Extracts Of White Watermelon (Citrullus vulgaris Schrad) Part of Kidney Health In Animal Trying Mice - Pujianti B. Donuata; Muhaimin Rifa'i; Unggul P. Juswono (Natural B, Journal of Health and Environmental Sciences, 2014)
Cancer is a worldwide problem. People take medication in late stadium therefore radioteraphy plays important role in healing cancer. Side effect of cancer therapy such as cancers of urethra, colon, stomach or rectum may have bad influence for kidney which causes the decrease kidney function. Goal of this research is to understand the influence of gamma radiation on urine and kidney tubules necrosis. Mice assigned into two groups, which are extract and non-extract radiation groups. Each group has five variations of radiation doses, including 200rad, 250rad, 300rad, 350rad, and 400rad. White part extract of watermelon (Citrullus vulgaris Schrad) also used with five variations including 0.3mL, 0.6mL, 0.9mL and 1.2mL. Non-extract radiation group was only exposed to radiation without treatment with white part extract of watermelon. Profile of kidney health can be seen from the percentage of epithelium, erythrocyte and leukocyte after mice were put into metabolism cage for 24hours and percentage of kidney tubules necrosis observed under Microscope BX-51 and analyzed with Ms.Excel. Result of research concludes that gamma radiation increase epithelium, erythrocyte and leukocyte in urine, and kidney tubules necrosis. White part extract of watermelon can improve kidney health by reducing the percentage of epithelium, erythrocyte leukocyte and kidney tubules necrosis of mouse.